SUSTAINABLE DEVELOPMENT STRATEGY AND SYSTEMS FOR PROTECTED NATURAL AREAS (Scientific journal of the Fergana State University, 2023)
The article reveals the role and importance of the system of protected natural areas (PA) in the strategy of sustainable development. It is also justified that protected areas should be organized to preserve biological and landscape diversity and ensure the environmentally sustainable development of the region.